Las actividades lúdicas y su incidencia en el desarrollo de la motricidad gruesa en los niños del tercer año de educación básica de la escuela Luis Felipe Borja de la parroquia de Toacaso cantón Latacunga durante el periodo abril-agosto del 2015 - Pallasco Tigse, Luis Freddy (2015)
This researching had as achievement diagnosing the development of gross motricity skills through leisure activities for children in the third year of basic education in order to comprehensively apply integrally their skills so both motor and intellectual, which itallowed to carry out strategies, which teachinng learnin process definitions of developing importance of developing gross motricity skills in children in the teaching process for this reason we propose leisure activities as a way to detect such problems….